Evaluation of the sensitivity and specificity of monoclonal antibodies for detecting the thioredoxin antigen in hepatocellular carcinoma patients - Huy, Duong Quang; Giang, Ho Truong; Diem, Nguyen Thi; Thuy, Vo Thi Bich (Edelweiss Applied Science and Technology, 2025)
The objective of this study was to evaluate the sensitivity and specificity of the monoclonal antibody of thioredoxin (mAb-TXN) for detecting the thioredoxin (TXN) antigen in serum samples from patients with hepatocellular carcinoma (HCC). To achieve this, the mAb-TXN, generated from hybridoma cells, was utilized to optimize the conditions for an indirect ELISA immunoassay. The sensitivity, specificity, positive predictive value, and negative predictive value of the assay were evaluated on the basis of stored patient medical records. The results showed that indirect ELISA using mAb-TXN exhibited a sensitivity of 93.61%, a specificity of 96%, a positive predictive value of 97.77%, and a negative predictive value of 88%. In conclusion, mAb-TXN is a valuable tool for detecting TXN antigens in serum samples from HCC patients, offering high sensitivity and specificity for clinical application.